Perlindungan Hukum terhadap Pembeli yang Beritikad Baik Terkait Jual Beli Tanah dan Implikasinya: Studi Kasus Putusan Mahkamah Agung, Nomor 2943/K/Pdt/2016 - Suparman, Maman; Pratama, Panji (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2024)
The issue of buying and selling cannot be separated from everyday community life, and good intentions in buying and selling are crucial factors. This ensures that buyers with good intentions will receive legal protection in accordance with applicable laws and regulations. Good intentions in buying and selling are closely related to land transactions, as land plays a vital role in national development. This raises the question of the position of buyers with good intentions in land transactions carried out by PT Jasa Marga (Persero) and the position of legal entities acquiring land rights. This study uses a normative juridical research method. The position of PT Jasa Marga (Persero) in the purchase of a piece of land under SHM Number 3147 in the name of Dewi Astuti is seen as a buyer with good intentions. Despite the legal defect in the object of the transaction due to the issuance of a certificate based on a fake document, which fails to meet the objective requirements of an agreement, PT Jasa Marga (Persero) is considered a bona fide buyer. Therefore, they should receive legal protection under the prevailing laws. The legal consequences of the ownership of the land acquired by PT Jasa Marga (Persero) through the transfer of rights between Dewi Astuti and PT Jasa Marga (Persero) are invalid. As a legal entity, PT Jasa Marga (Persero) cannot have ownership rights to land in the form of full ownership; a legal entity can only have land rights under certain conditions, such as the Right to Cultivate, Right to Build, and Right to Use as stipulated in Article 30, Article 36, and Article 42 of UUPA Number 5 of 1960.